2010
DOI: 10.1186/1757-1626-3-19
|View full text |Cite
|
Sign up to set email alerts
|

Deep wound infection after a trochanteric fracture internal fixation presenting with hip dislocation: a case report

Abstract: We report a rare case of posterior hip dislocation after a low energy trauma. The patient sustained a trochanteric fracture in the same hip six months ago, which was fixed using a sliding hip screw and had healed. At surgery a deep wound infection was found and a methicillin-resistant Staphylococcus epidermidis (MRSE) was cultured. After thorough debridement, an excisional arthroplasty was decided. The patient received specific intravenous antibiotics and after six weeks a total hip arthroplasty was done. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…One was managed by single stage where as the second case required two-stage surgery (spacer of antibiotic-impregnated cement modeled around a guidewire for the first stage). Tzurbakis et al ,22 reported a single case of deep wound infection after a trochanteric fracture internal fixation presenting with hip dislocation for which excisional arthroplasty was done as first stage and THA was done 6 weeks later. Our study has a series of 20 patients of failed infected internal fixation of hip.…”
Section: Discussionmentioning
confidence: 99%
“…One was managed by single stage where as the second case required two-stage surgery (spacer of antibiotic-impregnated cement modeled around a guidewire for the first stage). Tzurbakis et al ,22 reported a single case of deep wound infection after a trochanteric fracture internal fixation presenting with hip dislocation for which excisional arthroplasty was done as first stage and THA was done 6 weeks later. Our study has a series of 20 patients of failed infected internal fixation of hip.…”
Section: Discussionmentioning
confidence: 99%
“…12 Once a septic subluxation has occurred with associated changes in the femoral head and acetabulum, the only viable treatment option is debridement and resection arthroplasty followed by a replacement procedure later. [1][2][3]6 The authors believe that subluxation without hip pain after surgery should be viewed with concern and should raise the suspicion of a deep-seated infection. Subtle hip subluxation and increased medial joint space are often missed on radiographs and only detected retrospectively; however, these can be very early and reliable radiographic signs pointing to a deep septic process in a postoperative hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…Most have been reported to occur after trochanteric fracture fixation with a screw-plate combination. [1][2][3][4] A subluxation or dislocation after internal fixation of femoral neck fractures is even more uncommon, and almost all reported cases involve basicervical fractures fixed with a screw-plate combination. [5][6][7][8] To the best of the authors' knowledge, hip subluxation or dislocation after fixation of a transcervical femoral neck fracture with a minimally invasive implant like a cannulated cancellous screw (CCS) has not been reported in the literature to date.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Tzurbakis in 2010 reported a 78-year-old female with a hip dislocation after a deep infection on a trochanteric fracture treated with a sliding hip screw [13] . Infection and hip joint laxity were the reasons to which the authors explained the dislocation.…”
Section: Discussionmentioning
confidence: 99%